Femicide and murdered women's children: which future for these children orphans of a living parent?. Issue 1 (December 2015) - Ferrara, Pietro; Caporale, Olga; Cutrona, Costanza; Sbordone, Annamaria; Amato, Maria; Spina, Giulia; Ianniello, Francesca; Fabrizio, Giovanna; Guadagno, Chiara; Basile, Maria; Miconi, Francesco; Perrone, Giacomo; et al.
Abstract Background To assess the prevalence of femicides in Italy over the last three years and the potential long lasting effects of these traumatic events for the children of a woman who dies a violent death. Methods The data used in this study come from an internet search for the number of femicides occurring in Italy between 1st January, 2012 and 31st October, 2014. Results The total number of femicides was 319; the average age of murdered women was 47.50 ± 19.26. Cold arms in the form of sharp object -mostly knives- have caused the death of 102/319 women; firearms were used in 87/319 cases; asphyxiation was the chosen method in 52/319 cases. About the place where the femicides occurred, 209/319 were committed inside the victim's house. Children of women who died a violent death were 417 with a total of 180 minors in less than three years. A total of 52/417 children were witness to the killing and, among these 30/52 were minors; in 18/417 cases, children were murdered together with their mother and among these 9/18 were minors. Conclusions Long-term studies are needed to ascertain what happens to these children, to understand what are the most appropriate psychological treatments, the best decisions about the contact with their father and the best placement for these children.